Early Stage Alterations in White Matter and Decreased Functional Interhemispheric Hippocampal Connectivity in the 3xTg Mouse Model of Alzheimer’s Disease - Manno, Francis A. M.; Isla, Arturo G.; Manno, Sinai H. C.; Ahmed, Irfan; Cheng, Shuk Han; Barrios, Fernando A.; Lau, Condon (Frontiers in Aging Neuroscience, 2019)
Alzheimer’s disease is characterized by amyloid-β plaques and neurofibrillary tangles. The 3xTg mouse model of Alzheimer’s disease progressively develops plaques and tangles, recapitulating the neuropathology of human Alzheimer’s disease. We investigated the 3xTg mouse model using diffusion tensor imaging, resting-state functional magnetic resonance imaging, and volumetry at 2 months of age prior to the development of intraneuronal plaque accumulation. The 3xTg had significant fractional anisotropy increase and radial diffusivity decrease in the cortex compared with wild-type controls, while axial diffusivity and mean diffusivity were similar. Ventricular volume in the 3xTg was four times larger compared with that of controls. Interhemispheric hippocampal connectivity was decreased in the 3xTg while connectivity in the caudate putamen was similar. This study provided valuable neuroimaging characterization of the 3xTg model at an early stage of Alzheimer’s disease progression. The results are important for translating animal research to humans.